Determinants of the role of the Zionist entity in the war on Syria Employment Opportunities and Risk Challenges - عجوب, عمار; محمد صقر,; دريد العيسى , (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The Zionist entity followed with concern and anticipation the interaction and development of events in Syria, but later realized that it would not remain immune from the consequences of this conflict due to the large number of regional and international players influencing the levels of this conflict, and the size of the imbalance caused by this conflict in the structure of the regional system and its strategic balances. Therefore, he worked on formulating a specific policy to confront the challenges created by the conflict in Syria, and to define the goals that he must achieve, taking advantage of the strategic imbalance that resulted from this conflict by employing it to obtain gains that consolidate his security and his position in the map of influence and interests in the Middle East.